PBDS Baru man claims Sarawakians disagree Malay language become key condition for citizenship - Borneo Post, (Kuching) (Borneo Post (Kuching), 2017)
KUCHING: A Parti Bansa Dayak Sarawak (PBDS) Baru man believes that Sarawakians would not agree to a suggestion by an academician from Peninsular Malaysia who proposed the requirement for Malaysian children to learn the Malay language before being given blue identity cards.